ANTIHYPERCHOLESTEROLEMIC AND ANTIATHEROGENIC POTENTIAL OF AQUEOUS EXTRACT OF ADANSONIA DIGITATA STEM BARK INDUCED BY HEATED PALM OIL SUPPLEMENTED WITH EGG YOLK IN RAT - BONABE, CHRISTIAN; NTCHAPDA, FIDELE; ATSAMO, ALBERT DONATIEN; DJIBRINE, SOUDY IMAR; LEMBA TOM, ESTHER NGO; FOUDA, YANNICK BEKONO; MIAFFO, DAVID; DIMO, THEOPHILE (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: Poor control of hypercholesterolemia which mediated by overproduction of reactive oxygen species and endothelial dysfunction leads to atherosclerosis. The present study aimed to investigate the antihypercholesterolemic and anti-atherogenic effects of Adansonia digitata (AD) in heated palm oil/cholesterol supplemented with egg yolk in rat. Methods: Quantitative phytochemical screening of aqueous extract of A. digitata was carried out to identify the phytoconstituents. In vitro and in vivo antioxidant potential was evaluated. The antihypercholesterolemic and anti-atherosclerosis activity of A. digitata was evaluated by inducing hypercholesterolemia in rats with heated palm oil/cholesterol diet supplemented with egg yolk for 10 w. At the end of the induction period, animals were divided into 5 groups of 8 rats each after 6 w of induction: Group I (normocholesterolemic rat, NCR), Group II (hypercholesterolemia rat, HCR), Group III (Atorvastatin 2 mg/kg), Groups IV (AD. 100 mg/kg) and V (AD. 200 mg/kg). Hemodynamic parameters, lipid profile, atherogenic indices and oxidative stress markers were evaluated. Results: Adansonia digitata significantly reduced the systolic arterial blood pressure (SBP), diastolic arterial blood pressure (DBP), pulsatile pressure (PP) and heart rate compared to the hypercholesterolemic group. Plant extract reveal important flavonoids and phenolic contents and has significant in vivo antioxidant efficacy. The higher dose (200 mg/kg) of the extract significantly reduced in the level of total cholesterol by 27.29 %, triglycerides by 27.60 % and the LDL-c by 36.04 % meanwhile the HDL-c increased by 277.47 % when compared to 5HPOC treated group. Atorvastatin (2 mg/kg) administered in addition to 5HPOC significantly improved in lipid profile as compared to untreated rats. Furthermore, the histopathological examination of aorta of 5HPOC-treated rats indicated that the aqueous extract of A. digitata significantly attenuated atherosclerosis lesions. Conclusion: The aqueous extract of A. digitata possessed antihypercholesterolemic and anti-atherogenic effects via modulation overproduction of reactive oxygen species and endothelial dysfunction.